The Dayah Ulama’s Views on Plurality and Tolerance in Aceh - Syarifuddin Syarifuddin (Program Doktor Akidah dan Filsafat Islam, 2020)
Dayah ‘ulama’ or teungku dayah occupy a unique position in Acehnese society. They are a source of reference in various religious issues and social issues that develop in society. As the founder and manager of the dayah, traditional Islamic education institutions, the ‘ulama’ or teungku dayah have cultural power in shaping and coloring the community’s knowledge and religious understanding. Therefore, their views regarding plurality and tolerance in Aceh are relevant to be studied to see one fragment in the opinions and attitudes of the ‘ulama’ or tengku and Acehnese society regarding diversity in Aceh. In general, the ‘ulama’ or teungku dayah interviewed in this study gave a complimentary view of the reality of pluralism in the Acehnese community both in terms of inter-religious and intra-Muslim relations. However, they provide limitations regarding the aspects that can be tolerated and which should be prohibited.